The Role of Diffusion MRI in Rectum Cancer Staging and Evaluation of Neoadjuvan Treatment Efficiency - Yildirim, Mustafa; Koc, Mustafa (Akad Doktorlar Yayinevi, 2020)
The correct staging of rectal cancer is very important for treatment. This study aims to show the contribution of diffusion-weighted imaging (DWI) to staging, to predict tumor differentiation and neoadjuvant chemoradiotherapy response using DWI. The study consisted of 36 patients and 22 control groups. 12 patients who received neoadjuvant therapy were evaluated before and after treatment. Magnetic Resonance Imaging (MRI) and DWI were performed to all patients and apparent diffusion coefficient (ADC) maps were obtained. The findings were compared with histopathological results. T staging accuracy was 72.2% on MRI. N staging accuracy rate was 75% on the T2 sequence and 72.2% on DWI. Tumoral rectal ADC values were significantly decreased compared to the normal rectal wall (p< 0.001). Mean T3 and T4 (extramural) ADC values were significantly decreased compared to the T2 stage (intramural) ADC values (p< 0.001). ADC and relative ADC (lymph node / primary tumor ADC) values of the metastatic lymph nodes were significantly decreased compared to benign lymph nodes (p< 0.001). According to the ADC cut point, N staging accuracy was found to be 83%. The ADC values of the low differentiated group were significantly decreased compared to the moderately and well-differentiated group (p< 0.011). In the control MRI of patients receiving neoadjuvant therapy, the ADC increase in the group that responded well to the treatment was significantly higher than the group with partial response (p <0.004). As a result, DWI and ADC are useful for preoperative rectum cancer evaluation.
Keywords: Rectum cancer; Staging; Diffusion MRI